The positive and negative effects of technology on children’s cognitive development from the perspective of their teachers (Journal of the College of Education for Women, 2025)
The current research aims to identify the positive and negative effects of technology on the cognitive development of children from the point of view of their teachers, and to identify statistically significant differences in the positive and negative effects of technology on the cognitive development of children from the point of view of their teachers, depending on the gender variable (males, females), and to achieve my goal. For the research, a stratified random sample of (400) male and female teachers was chosen, distributed into (200) male and (200) male teachers, then a tool was prepared consisting of (15) items formulated in the style of self-report/declarative statements. The researchers verified the apparent validity of the scale and calculated its reliability. In the method of application and re-application, the Facronbach equation was also used, and the reliability coefficient values ​​were good compared to previous studies. The results of the research showed positive effects of the scale’s items, with (9) items, while (6) items appeared with negative effects on children’s cognitive development. The result of the second objective was the presence of statistically significant differences between male and female teachers in the negative effects, as the female teachers were more conservative. On the use of modern technology due to its negative effects, male and female teachers agreed on some of the others, and the two researchers came up with a set of recommendations and proposals in light of the research results